2005
DOI: 10.1042/bj20050145
|View full text |Cite
|
Sign up to set email alerts
|

Different phospholipase-C-coupled receptors differentially regulate capacitative and non-capacitative Ca2+ entry in A7r5 cells

Abstract: Several receptors, including those for AVP (Arg8-vasopressin) and 5-HT (5-hydroxytryptamine), share an ability to stimulate PLC (phospholipase C) and so production of IP3 (inositol 1,4,5-trisphosphate) and DAG (diacylglycerol) in A7r5 vascular smooth muscle cells. Our previous analysis of the effects of AVP on Ca2+ entry [Moneer, Dyer and Taylor (2003) Biochem. J. 370, 439-448] showed that arachidonic acid released from DAG stimulated NO synthase. NO then stimulated an NCCE (non-capacitative Ca2+ entry) pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 50 publications
2
17
0
Order By: Relevance
“…Despite the quantitative uncertainty of Western analysis, assessment of TRPC protein levels rather than mRNA levels is obviously a more reliable indicator of the presence and relative levels of endogenous TRPC channels. In a paper published after completion of this work, Moneer et al (36) revealed significant variations in the expression of TRPC channels in different strains of A7r5 cells. In certain strains, significant levels of TRPC3 message could be detected, although no information on protein levels was given.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the quantitative uncertainty of Western analysis, assessment of TRPC protein levels rather than mRNA levels is obviously a more reliable indicator of the presence and relative levels of endogenous TRPC channels. In a paper published after completion of this work, Moneer et al (36) revealed significant variations in the expression of TRPC channels in different strains of A7r5 cells. In certain strains, significant levels of TRPC3 message could be detected, although no information on protein levels was given.…”
Section: Resultsmentioning
confidence: 99%
“…AA appears also to differ in its effectiveness according to how it is produced. We have shown earlier that release of AA by DAG lipase from DAG produced by AVP-activated PLC causes reciprocal regulation of CCE and NCCE [6,7], but the much larger amounts of AA produced by cPLA 2 (Fig. 1) appear not to significantly influence Ca 2+ entry (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A7r5 vascular smooth muscle cells, although their relative roles may differ under different conditions [4][5][6][7][8][9], influenced by both the pattern of expression of TrpC proteins [7,10] and the nature of the stimulus [7]. It is, however, clear that in A7r5 cells, as in many other cells [11][12][13], arachidonic acid (AA) contributes to the coordinate regulation of CCE and NCCE [5,6,14].…”
Section: -Vasopressin (Avp) Inmentioning
confidence: 99%
See 2 more Smart Citations